A selective sweep driven by pyrimethamine treatment in southeast asian malaria parasites. - Nair, S; Williams, J; Brockman, A; Paiphun, L; Mayxay, M; Newton, P; Guthmann, J; Smithuis, F; Hien, T; White, N; Nosten, F; Anderson, T (2003)
Malaria parasites (Plasmodium falciparum) provide an excellent system in which to study the genomic effects of strong selection in a recombining eukaryote because the rapid spread of resistance to multiple drugs during the last the past 50 years has been well documented, the full genome sequence and a microsatellite map are now available, and haplotype data can be easily generated. We examined microsatellite variation around the dihydrofolate reductase (dhfr) gene on chromosome 4 of P. falciparum. Point mutations in dhfr are known to be responsible for resistance to the antimalarial drug pyrimethamine, and resistance to this drug has spread rapidly in Southeast (SE) Asia after its introduction in 1970s. We genotyped 33 microsatellite markers distributed across chromosome 4 in 61 parasites from a location on the Thailand/Myanmar border. We observed minimal microsatellite length variation in a 12-kb (0.7-cM) region flanking the dhfr gene and diminished variation for approximately 100 kb (6 cM), indicative of a single origin of resistant alleles. Furthermore, we found the same or similar microsatellite haplotypes flanked resistant dhfr alleles sampled from 11 parasite populations in five SE Asian countries indicating recent invasion of a single lineage of resistant dhfr alleles in locations 2000 km apart. Three features of these data are of especially interest. (1). Pyrimethamine resistance is generally assumed to have evolved multiple times because the genetic basis is simple and resistance can be selected easily in the laboratory. Yet our data clearly indicate a single origin of resistant dhfr alleles sampled over a large region of SE Asia. (2). The wide valley ( approximately 6 cM) of reduced variation around dhfr provides "proof-of-principle" that genome-wide association may be an effective way to locate genes under strong recent selection. (3). The width of the selective valley is consistent with predictions based on independent measures of recombination, mutation, and selection intensity, suggesting that we have reasonable estimates of these parameters. We conclude that scanning the malaria parasite genome for evidence of recent selection may prove an extremely effective way to locate genes underlying recently evolved traits such as drug resistance, as well as providing an opportunity to study the dynamics of selective events that have occurred recently or are currently in progress.